2022
DOI: 10.1108/ijhma-05-2022-0067
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of millennials’ acceptance towards tawarruq home financing in Sandakan, Sabah, Malaysia

Abstract: Purpose The purpose of this study was to investigate the factors that influence the millennials’ intention to choose tawarruq home financing in Sandakan, Sabah, Malaysia. Design/methodology/approach The primary data were gathered via the questionnaire survey administered among Islamic banking customers in Sandakan, Sabah. Data obtained were analysed via multiple regression analysis using the software, Statistical Package for Social Sciences. Findings This study found that attitude, subjective norm, perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Furthermore, we delve into the examination of the most extensively tested theories in CB research (in accordance with the suggestions provided by Canabal and White, 2008;Roy Bhattacharjee et al, 2022). The application of inter-related theories of TRA and TPB, SERVQUAL and CARTER model and TAM and unified theory of acceptance and use of technology (UTAUT) in the IB (Ajzen, 1991) is the other prominent theory that is often used in conjunction with TRA to detail consumer adoption of IB and IB products (Abou-Youssef et al, 2015;Johan et al, 2020;Asyari et al, 2022;Panggi et al, 2022). TPB is an extension of TRA, including an additional factor of perceived behavioral control.…”
Section: Theory-context-characteristics-methods Framework 41 Theoriesmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, we delve into the examination of the most extensively tested theories in CB research (in accordance with the suggestions provided by Canabal and White, 2008;Roy Bhattacharjee et al, 2022). The application of inter-related theories of TRA and TPB, SERVQUAL and CARTER model and TAM and unified theory of acceptance and use of technology (UTAUT) in the IB (Ajzen, 1991) is the other prominent theory that is often used in conjunction with TRA to detail consumer adoption of IB and IB products (Abou-Youssef et al, 2015;Johan et al, 2020;Asyari et al, 2022;Panggi et al, 2022). TPB is an extension of TRA, including an additional factor of perceived behavioral control.…”
Section: Theory-context-characteristics-methods Framework 41 Theoriesmentioning
confidence: 97%
“…TRA posits that an individual’s behavior is influenced by their attitudes toward the behavior and their perception of social pressures and expectations surrounding it. The first line of inquiry indicates how the attitude of different customers, specifically millennial generations (Farhat et al , 2019; Asyari et al , 2022; Panggi et al , 2022) and religious leaders(Janah et al , 2020), influence behavioral intention toward IB and IB products use (credit card – Ali et al , 2017; Johan et al , 2020; takaful – Farhat et al , 2019; Tawarruq – Panggi et al , 2022) The second line of research detail the factors affecting customer attitude toward IB adoption (Amin, 2013; Kaakeh et al , 2019) in specific countries (for example, UAE: Kaakeh et al , 2019; Malaysia: Amin, 2013; Mauritius: Omran et al , 2022). Based on this theory, apart from attitude and subjective norms, the factors such as religiosity (Abou-Youssef et al , 2015; Panggi et al , 2022), religious status (Omran et al , 2022), religious obligation (Janah et al , 2020), IB knowledge (Ezeh and Nkamnebe, 2020) and financial investment (Amin, 2013; Ali et al , 2017; Asyari et al , 2022) were observed to influence the behavioral intention.…”
Section: Theory-context-characteristics-methods Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Maduku and Mbeya (2023) discovered that PBC affects Sharia compliance behaviour in Sharia financial products significantly and positively. Panggi et al (2022) discovered that behavioural control has a substantial positive link with the millennial generation's desire for Tawarruq products in Sandakan, Sabah, indicating that the millennial generation follows religious laws. According to the findings of Gilal et al (2022), Muslims' consumption patterns are affected by their perceptions of behavioural control.…”
Section: Eligibilitymentioning
confidence: 99%
“…Amin (2022) examined the effect of attitude on the intention to give alms online among students in Malaysia and showed that attitude is the most influential variable. Panggi et al (2022) analyzed millennials' acceptance of Tawarruq home financing in Sandakan, Sabah and Malaysia, and showed that attitude is the most influential variable. Based on this explanation, the hypotheses of this research are:…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%